Situation Report: Bulgaria, 2 July 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Janos Kadar to Visit Bulgaria Meeting of the Ministerial Council Reaction to Nixon's Forthcoming Visit to Romania and Heinemann's Inauguration as West German President Bulgarian Writers and Sportsmen to Cooperate Bulgarian-Yugoslav Protocol Signed